PENDEKATAN TRANSDISIPLINER SEBAGAI KERANGKA PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS MASALAH GLOBAL KOMPLEKS - Mujiburrohman; Muhammad Naufal Alauddin; Munawarah; Andi Cahyuni Candrawati; Sonia Isna Suratin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In the era of globalization and the complexity of global challenges, education faces pressure to produce graduates who are able to think critically, adaptively, and provide solutions to global problems such as climate change, social inequality, and the technological crisis. At the national level, educational curricula are often sectoral and partial, thus failing to prepare students to face the dynamics of global problems holistically. The urgency of this study arises from the need for innovative pedagogical strategies that can bridge the learning of disciplinary concepts with the real application of complex problems, while being relevant for the development of 21st-century education. This study aims to analyze the transdisciplinary approach as a framework for developing a learning model based on complex global problems, emphasizing its contribution to the integration of knowledge, values, and critical thinking skills of students. The study used a qualitative approach with a literature study method. Data were collected from primary and secondary sources in the form of educational theory books, international journal articles, curriculum policies, and research reports related to transdisciplinary learning. Data analysis was conducted descriptively and analytically using conceptual and comparative synthesis techniques, and data validity strategies through source triangulation and expert validation. The results show that the transdisciplinary approach enables the integration of cross-disciplinary perspectives, improves complex problem-solving abilities, and encourages contextual learning that is relevant globally and locally. The developed model of complex global problem-based learning emphasizes collaboration, critical reflection, and real-world applicability. The implications of this study confirm its theoretical contribution in expanding the holistic education paradigm and its practical implications for educators in designing innovative learning strategies responsive to global challenges.